Design and synthesis of a biaryl series as inhibitors for the bromodomains of CBP/P300. Issue 1 (1st January 2018) - Lai, Kwong Wah; Romero, F. Anthony; Tsui, Vickie; Beresini, Maureen H.; de Leon Boenig, Gladys; Bronner, Sarah M.; Chen, Kevin; Chen, Zhongguo; Choo, Edna F.; Crawford, Terry D.; Cyr, Patrick; Kaufman, Susan; et al.
Graphical abstract: Abstract: A novel, potent, and orally bioavailable inhibitor of the bromodomain of CBP, compound 35 (GNE-207), has been identified through SAR investigations focused on optimizing al bicyclic heteroarene to replace the aniline present in the published GNE-272 series. Compound 35 has excellent CBP potency (CBP IC50 = 1 nM, MYC EC50 = 18 nM), a selectively index of >2500-fold against BRD4(1), and exhibits a good pharmacokinetic profile.